(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Engineering education is undergoing rapid transformation due to the increasing complexity of technological systems, the diversification of industrial requirements, and the shift toward competency-based learning models. Developing professional competence has become a central priority for preparing future engineers capable of solving practical problems, making informed decisions, and adapting to real production environments. This article examines the scientific foundations of shaping professional competence in engineering education, focusing on theoretical, methodological, psychological, and didactic principles that determine the structure, mechanisms, and assessment of competence formation.